Bilingual Mongolian students’ attitudes, perceptions, and beliefs on the process of foreign language policy and language planning implementation in an eastern Mongolian university - Na, Jian (2020)
This research examined why bilingual Mongolian students chose to learn Japanese as their foreign language at university and how their perceived experiences' impact on foreign language policy and language planning implementation from university, classroom, to self-learning level. Drawing upon data collected through analysis of documents, student questionnaire and semi-structured interviews, the study found that the enactment of China’s systemic College Japanese Curriculum from one eastern Mongolian university was not a matter of simple implementation but the result of a more complex process, which changes in language context to shape students’ language attitudes, perceptions, beliefs, motivations and actions as regards to Japanese learning. The research, therefore, argues that multi-level contents and cause-effect sequences intertwined to shape Mongolian students’ language cognitions and behaviours of Japanese teaching and learning.